Seleksi dan Evaluasi Mutu Beras Padi Gogo Adaptif Lahan Kering Masam - Yullianida; Lestari, Angelita Puji; Hermanasari, Rini; Hairmansis, Aris (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2021)
Improvement upland rice lines are faced with the diversity of physical and ecobiological characteristics of dry land, including acidic-dry land. An alternative approach to optimize upland rice cultivation in acidic-dry land is the selection of adaptive varieties. The aim of this experiment was to obtain lines that have superior performance and yield on acidic-dry land, as well as good rice quality. A total of 36 lines of upland rice, including four check varieties, were selected at Tamanbogo, Lampung on rainy season (November 2017-March 2018). The genetic parameters estimation showed that flowering age, harvest age, weight of 1,000 grains and yield can be used as selection criteria. Based on these selection criteria, four lines were selected, namely B15231-MR-10-1, B15053F-PWR-2, B14908C-MR-1-25-1-3 and B15344B-TB-34. These lines had grain yields that were not significantly different from the best check variety Inpago 8 (3.84 ton ha-1), average resistant to leaf blast (score 1), highly resistant to neck blast (score 0), and moderately tolerant of Al. Additionally, these lines had medium grain with small-medium chalkiness (MMS-LMM), amylose content between 20-23% with soft-medium rice texture. One selected line, namely B15344B-TB-34, was identified as a red-pericarp rice. Keywords: aluminum toxicity, blast disease, drought, grain quality, selection criteria